2006
DOI: 10.1210/jc.2006-1668
|View full text |Cite
|
Sign up to set email alerts
|

High Prevalence of Pituitary Adenomas: A Cross-Sectional Study in the Province of Liège, Belgium

Abstract: The prevalence of pituitary adenomas in the study population (one case in 1064 individuals) was more than 3.5-5 times that previously reported. This increased prevalence may have important implications when prioritizing funding for research and treatment of pituitary adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
525
8
47

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 907 publications
(606 citation statements)
references
References 14 publications
(20 reference statements)
26
525
8
47
Order By: Relevance
“…1,2 Virtually all organs or tissues are affected directly or indirectly by the hormones secreted by the anterior pituitary. 3,4 Pituitary adenomas result of a multistep process in which the multi-causal and inherited genetic predisposition, endocrine factors, and specific somatic mutations are factors that may contribute to their development.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Virtually all organs or tissues are affected directly or indirectly by the hormones secreted by the anterior pituitary. 3,4 Pituitary adenomas result of a multistep process in which the multi-causal and inherited genetic predisposition, endocrine factors, and specific somatic mutations are factors that may contribute to their development.…”
Section: Introductionmentioning
confidence: 99%
“…3 A population-based study conducted in the province of Liège, Belgium, reported a 3-5 times higher prevalence of clinically relevant pituitary tumours (1:1064) than previously estimated. 4 Pituitary adenomas are generally associated with hormone overproduction and/or compression signs and symptoms due to the impingement of adjacent structures, including optic chiasm. [5][6][7][8][9][10][11] Symptoms are related to their size and position: if the adenoma is larger than 10 mm in diameter ('macroadenoma') it can extend beyond the limits of the sella and can cause neuroophthalmologic disorders by compressing the adjoining structures.…”
Section: Introductionmentioning
confidence: 99%
“…In this study only few (3/76) tumours were identified as macroadenomas corresponding to a tumour size >10 mm. (Buurman, 2006) The prevalence of clinically apparent prolactinomas ranges from 6-50/ 100,000 in reported populations (Daly, 2006;Fernandez 2010). The prevalence of "ever-treated" hyperprolactinemia is approximately 20 /100,000 in male patients and approximately 90 /100,000 in female patients.…”
Section: Characteristics Of Pituitary Adenomasmentioning
confidence: 99%